2022
DOI: 10.1093/ofid/ofac066
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Against SARS-CoV-2 Is Associated With a Lower Viral Load and Likelihood of Systemic Symptoms

Abstract: Background Data conflict on whether vaccination decreases severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) viral load. The objective of this analysis was to compare baseline viral load and symptoms between vaccinated and unvaccinated adults enrolled in a randomized trial of outpatient COVID-19 treatment. Methods Baseline data from the first 433 sequential participants enrolling into the COVID-OUT trial were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 15 publications
6
21
0
Order By: Relevance
“…These observations are consistent with the reduction of neutralizing antibodies against Omicron observed in experimental studies (20,21) and a notable duration of infectious shedding of the Omicron virus in vaccinated persons (22). The protective effect of vaccination against SARS-CoV-2 infection in the Delta-dominant period was consistent with previous reports on the Delta VOC, which had similar but limited results (6,21,(23)(24)(25)(26). However, we could not ascertain if the booster dose was effective for reducing transmission, likely because of the low sample size (only 46 contacts had booster vaccines administered during the Delta-dominant period).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These observations are consistent with the reduction of neutralizing antibodies against Omicron observed in experimental studies (20,21) and a notable duration of infectious shedding of the Omicron virus in vaccinated persons (22). The protective effect of vaccination against SARS-CoV-2 infection in the Delta-dominant period was consistent with previous reports on the Delta VOC, which had similar but limited results (6,21,(23)(24)(25)(26). However, we could not ascertain if the booster dose was effective for reducing transmission, likely because of the low sample size (only 46 contacts had booster vaccines administered during the Delta-dominant period).…”
Section: Discussionsupporting
confidence: 90%
“…However, we could not ascertain if the booster dose was effective for reducing transmission, likely because of the low sample size (only 46 contacts had booster vaccines administered during the Delta-dominant period). The protective effect against the Delta variant diminished as the time since vaccination increased, which has also been previously reported (5,24,26). Our estimates suggest a nonlinear trend for reduction of vaccine protection, culminating at ≈20 weeks after vaccination.…”
Section: Discussionsupporting
confidence: 84%
“…We also assumed that the infectivity of those with SARS-CoV‑2 infection would be similar irrespective of vaccination status. While several studies have found similar viral loads independent of vaccine status [ 7 , 8 ], some studies have found that if vaccinated within 6 months before developing COVID-19, the viral loads might be lower [ 9 ]. Some studies have also suggested that viral loads decrease more rapidly in those who were vaccinated versus those who are unvaccinated [ 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the observed difference in gene copy number/imputed viral load is that during the initial Omicron surge, a greater proportion of the population may have acquired some degree of immunity through vaccination or prior infection. Some reports support the idea of attenuated viral load with vaccination [49][50][51] while others suggest no significant difference between unvaccinated and vaccinated individuals [52][53][54].…”
Section: Viral Gene Copiesmentioning
confidence: 99%